Seasonal effect and long-term nutritional status following exit from a Community-Based Management of Severe Acute Malnutrition program in Bihar, India - Sakib Burza; Raman Mahajan; Elisa Marino; Temmy Sunyoto; Chandra Shandilya; M S Tabrez; K Kumar; Arsh Jha; Prince Mathew; Núria Salse; Cristian Casademont; Neha Mishra (2015)
Children aged 6 months to 5 years completing treatment for severe acute malnutrition (SAM) in a Médecins Sans Frontières Community Management of Acute Malnutrition (CMAM) program in Bihar, India, showed high cure rates; however, the program suffered default rates of 38%. This report describes the nutritional status of 1956 children followed up between 3 and 18 months after exiting the program.All children aged 6-59 months discharged as cured with mid-upper arm circumference (MUAC) ⩾120 mm or who defaulted from the program with MUAC <115 mm were traced at 3, 6, 9, 12 and 18 months (±10 days) before three exit reference dates: first at the end of the food insecure period, second after the 2-month food security and third after the 4-month food security.Overall, 68.7% (n=692) of defaulters and 76.2% (n=1264) of children discharged as cured were traced. Combined rates of non-recovery in children who defaulted with MUAC <115 mm were 41%, 30.1%, 9.9%, 6.1% and 3.6% at 3, 6, 9, 12 and 18 months following exit, respectively. Combined rates of relapse among cured cases (MUAC ⩾120 mm) were 9.1%, 2.9%, 2.1%, 2.8% and 0% at 3, 6, 9, 12 and 18 months following discharge, respectively. Prevalence of undernutrition increased substantially for both groups traced during low food security periods. Odds of death were much higher for children defaulting with MUAC <110 mm when compared with children discharged as cured, who shared the same mortality risk as those defaulting with MUAC 110-<115 mm.Seasonal food security predicted short-term nutritional status after exit, with relapse rates and non-recovery from SAM much higher during food insecurity. Mortality outcomes suggest that a MUAC of 110 mm may be considered an appropriate admission point for SAM treatment programs in this context.